STRUKTUR SEMANTIK ONOMATOPE BAHASA INDONESIA PENDEKATAN METABAHASA SEMANTIK ALAMI - Nurhidayati, Siti Ayu; Mulyadi, Mulyadi (STKIP Siliwangi, 2024)
This research aims to describe the types of Indonesian onomatopoeia and describe the original meaning of Indonesian onomatopoeic verbs to be simple so that it is easily understood by cross-linguistic people. The method used is descriptive qualitative method. Data collection techniques by observing and recording data obtained from written media, such as textbooks and websites. The findings obtained from this research are that there are four types of Indonesian onomatopoeia, namely human voices, animal voices, natural sounds, sounds of various kinds of sound imitations. Some semantic structures of verbs show similarities and differences, namely differences in intention and desire from state verbs, process verbs, and action verbs. The semantic structures of calling verbs (piyaak-piyak-piyaak, ssshh-ssshh), stopping verbs (ti), and thumping verbs (bush-bush-bush) have purposive factors and desires. Similarly, the group of attacking verbs (eh hok hik, gludug-gludug, klontang, tet-tet-tet) have purposive and desirability factors. However, in the group of generating verbs (glug-glug-glug, uhuk-uhuk), falling verbs (bruk), and blowing verbs (whoosh) have no intentionality and are not purposive. The use of onomatopoeia has the benefit of creating a more vivid sound effect in the work so that readers can better feel the atmosphere of the story.